An insight into artisanal leather making in Ghana - Miriam Appiah-Brempong; Helen M. K. Essandoh; Nana Yaw Asiedu; Samuel Kwame Dadzie; Francis Warings Yao Momade (Journal of Leather Science and Engineering, 2020)
Abstract The production of leather from animal skins and hides through tanning processes began in the pre-historic ages. Despite the origination of new leather making techniques such as chrome tanning which is being employed extensively today, the traditional method of leather production primarily through vegetable tanning is still being practised mostly in artisanal tanneries in developing nations including Ghana. Artisanal leather making, thus, contributes beneficially to rural livelihood. Nevertheless, the growth of this sector has been stifled by the lack of innovative technologies to enhance productivity. This challenge could be partly linked to the knowledge gap on the scientific principles governing artisanal leather production processes. This study, therefore, elaborates on various process steps and materials employed in traditional leather making in Ghana and the scientific principles underlying each of the processes. It also makes a comparison between traditional and modern leather manufacturing processes and identifies knowledge and technological gaps which would inspire in-depth scientific research into artisanal leather making. Graphical abstract